NeoRAS wild-type in metastatic colorectal cancer: Myth or truth?—Case series and review of the literature. (August 2021) - Osumi, Hiroki; Vecchione, Loredana; Keilholz, Ulrich; Vollbrecht, Claudia; Alig, Annabel H.S.; von Einem, Jobst C.; Stahler, Arndt; Striefler, Jana K.; Kurreck, Annika; Kind, Andreas; Modest, Dominik P.; Stintzing, Sebastian; et al.
Abstract: Upfront KRAS and NRAS gene testing (' RAS ') is the standard of care for metastatic colorectal cancer (mCRC), to guide first-line treatment. The presence of RAS mutation (MT) is a negative predictor for the efficacy of anti-EGFR antibodies and the use of cetuximab and panitumumab is restricted to RAS wild-type (WT) mCRC. Conversion from RAS WT to RAS MT mCRC after treatment with anti-EGFR antibodies is a known and well-described acquired resistance mechanism. The by far less frequent 'Neo RAS wild-type' phenomenon (reversion from RAS MT to RAS WT) has recently drawn attention. The proposed effect of chemotherapy on RAS status in mCRC patients is not fully understood. Because of the intriguing biological consequence of a RAS MT to RAS WT reversion, subsequent treatment of Neo RAS WT patients with anti-EGFR antibodies is increasingly being discussed. Here, we report three clinical cases of Neo RAS WT mCRC patients, which received standard-of-care regimens for RAS MT mCRC. Anti-EGFR antibodies were used in two out of three patients after progression of the disease. One of the patients had a long-term response. In line with our observations, Neo RAS WT phenomenon occurs in clinical practice. Retesting of RAS status during treatment should be discussed in patients with unusual long-term clinical courses of RAS MT mCRC to optimise treatment strategy and to evaluate the use of anti-EGFR antibodies. Highlights: RAS gene status could be changed before and after the chemotherapy. mCRC patients with Neo RAS wild-type could gain the benefit from EGFR inhibitor. Retesting of RAS genes contributes to optimise treatment strategy of EGFR inhibitor.